LncRNA LOXL1-AS1 Promotes the Proliferation and Metastasis of Medulloblastoma by Activating the PI3K/AKT Pathway - Ran Gao; Rui Zhang; Cuicui Zhang; Yingwu Liang; Weining Tang (Analytical Cellular Pathology)
Medulloblastoma is the most common malignant brain tumor of childhood, with great potential to metastasize. However, the mechanisms of how medulloblastoma develops and progresses remain to be elucidated. The present study assessed the role of long noncoding RNA LOXL1-AS1 (lncRNA LOXL1-AS1) in the cell proliferation and metastasis in human medulloblastoma. It was initially found that LOXL1-AS1 was significantly overexpressed in clinical medulloblastoma tissues compared with the adjacent noncancerous tissues. LOXL1-AS1 was also highly expressed in medulloblastoma at advanced stages and differentially expressed in a series of medulloblastoma cell lines. Knockdown of LOXL1-AS1 using shRNAs significantly inhibited cell viability and colony formation capacities in D283 and D341 cells. Moreover, the cell proportion in the S phase was significantly increased, while the cell proportion in the G2/M phase was decreased after knockdown of LOXL1-AS1 in D283 cells and D341 cells. Cell cycle arrest led to eventual cell apoptosis by LOXL1-AS1 knockdown. Moreover, in a xenograft model of human medulloblastoma, knockdown of LOXL1-AS1 significantly inhibited tumor growth and promoted tumor cell apoptosis. In addition, knockdown of LOXL1-AS1 inhibited cell migration and reversed epithelial-to-mesenchymal transition (EMT). Western blot analysis further revealed that knockdown of LOXL1-AS1 decreased the phosphorylated levels of PI3K and AKT without affecting their total protein levels. These results suggest that LncRNA LOXL1-AS1 promoted the proliferation and metastasis of medulloblastoma by activating the PI3K-AKT pathway, providing evidence that knockdown of LncRNA LOXL1-AS1 might be a potential therapeutic strategy against medulloblastoma.